1992
DOI: 10.1007/bf01296504
|View full text |Cite
|
Sign up to set email alerts
|

Assessment by prolonged ambulatory manometry of the effect of oral cisapride on proximal small bowel inter-digestive motility

Abstract: The effects of cisapride, given orally at standard therapeutic dosage (10 mg tds), on proximal small bowel interdigestive motility in ten healthy volunteers was assessed by prolonged ambulatory manometry. Cisapride did not alter the duration of the MMC cycle, duration of phase II or the propagation rate of phase III in either the daytime or nighttime periods. However, when compared to studies, in which subjects received no drug, both nighttime and daytime phase II mean contractile amplitude, but not contractil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…*P < 0.05 compared with control period. , while cisapride, also a 5-HT4-receptor agonist, given orally or parenterally to healthy volunteers, did not induce phase I11 activity or increase its propagation velocity [28,29]. Possible explanations for the disparate results obtained in dogs and man are species differences as well as differences between the two compounds renzapride and cisapride.…”
Section: Plasma Concentration (Nmol/l) Of Lht During Infusion Of Lht mentioning
confidence: 95%
“…*P < 0.05 compared with control period. , while cisapride, also a 5-HT4-receptor agonist, given orally or parenterally to healthy volunteers, did not induce phase I11 activity or increase its propagation velocity [28,29]. Possible explanations for the disparate results obtained in dogs and man are species differences as well as differences between the two compounds renzapride and cisapride.…”
Section: Plasma Concentration (Nmol/l) Of Lht During Infusion Of Lht mentioning
confidence: 95%
“…56 Through application of the mixed effects model, an estimate for the effect of RH or NS patients over CS, its 95% confidence interval (CI), and its statistical significance were calculated. 57 In order to maintain normal distribution of residuals (random errors) in the mixed effects model, data for each RMC variable were first transformed logarithmically to derive a single summary statistic for each individual, and the expected effect and its 95% confidence interval from the model were then antilog transformed. Using this methodology, the estimated effect for a variable should be interpreted as relative change.…”
Section: Rmc Variablesmentioning
confidence: 99%
“…Studies that have measured amplitudes of pressure waves have also shown an increase in amplitude as a result of cisapride treatment (9,11), or an increase in motility index (10), also likely to be a reflection of a higher amplitude of pressure waves. Two postprandial duodenal motility studies found no increase in number of pressure waves (11,13), as in the present study. One study in humans (12) found an increased incidence of jejunal contractions after a single dose of cisapride.…”
Section: -Omg Absorption and Cisapridementioning
confidence: 99%